The impact of regional supply and demand conditions on job creation and destruction - Raimund Krumm; Harald Strotmann (Institut für Angewandte Wirtschaftsforschung (IAW), 2010)
This paper gives an empirical analysis of the impact of regional conditions on regional manufacturing employment growth. Based upon a firm-level panel of manufacturing establishments in Baden-Wuerttemberg, Germany, which can be aggregated to regional panel data for forty-four counties, both the role of supply-side and demand-side conditions and a possible impact of characteristics of the regional industry structure on regional employment growth are analysed for the period from 1980 to 1999. Moreover, the paper examines whether the impact of regional conditions on regional net employment growth is driven by their impact on regional firm-level job creation and/or job destruction. Our results indicate that supply-side conditions seem to be more important for regional employment growth than demand-side factors. While lower costs of production lead to higher regional employment growth due to lower job destruction, a better endowment with human capital and a higher regional R&D intensity stimulate employment growth by higher rates of job creation. Differences in regional firm size structure, export intensity, and other industry structure aspects are affecting job creation, but not job destruction. Moreover, the analysis reveals at least the tendency that regional location factors mainly influence either job creation or job destruction, but seldom both at the same time.
Keywords: R11; R3; O18; 330; Regional development; employment growth; job creation; job destruction; location conditions; manufacturing; Regionale Entwicklung; Regionaler Arbeitsmarkt; Beschäftigungseffekt; Verarbeitendes Gewerbe; Gesamtwirtschaftliches Angebot; Gesamtwirtschaftliche Nachfrage; Baden-Württemberg